Characterization and genome analysis of Vibrio phage vB_VhaP_PG11, representing a new viral genus - Jing, Yajun; Guo, Ruizhe; Wang, Hongmin; Liang, Yantao; Liu, Yundan; Feng, Yifei; Ma, Qin; Shao, Hongbing; Sung, Yeong Yik; Mok, Wen Jye; Wong, Li Lian; Zhang, Yu-Zhong; et al. (Frontiers in Marine Science, 2023)
In the study, a novel marine phage vB_VhaP_PG11, infecting Vibrio hangzhouensis, was isolated from the offshore waters of Qingdao, China. vB_VhaP_PG11 is a double-stranded DNA phage. The whole genome proteomic tree shows that vB_VhaP_PG11 phage is related to two Vibrio phages, Vibrio phage 1.238.A._10N.261.52.F10 and Vibrio phage 1.245.O._10N.261.54.C7, but with low homology. Their amino acids identity with vB_VhaP_PG11 is 42.77 and 41.49% respectively. The prediction results of genome-blast distance phylogeny (GBDP) and the analysis gene-sharing network indicate that vB_VhaP_PG11 belongs to a new genus in Schitoviridae, named Qingschitovirus. The study of Vibrio phage vB_VhaP_PG11 provides basic information contributing to a better understanding of interactions between Vibrio phages and their hosts and helps analyze unknown viral sequences in the metagenomic database.